ChemInform Abstract: Latent Ruthenium—Indenylidene Catalysts Bearing a N‐Heterocyclic Carbene and a Bidentate Picolinate Ligand. Issue 49 (December 2015) - Schmid, Thibault E; Modicom, Florian; Dumas, Adrien; Borre, Etienne; Toupet, Loic; Basle, Olivier; Mauduit, Marc
Abstract: From a set of three novel precatalysts compound RIC gives the best results in ring‐closing, cross‐ and enyne metathesis reactions.